2015
DOI: 10.1007/s11908-015-0478-5
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Causing Deep Ulcerative Suppurative Vaginitis/Pyoderma Gangrenosum

Abstract: Pyoderma gangrenosum (PG) is a rare cause of purulent vulvovaginal ulceration. Six recent cases of vulvovaginal pyoderma gangrenosum associated with rituximab are described. All cases were seen in the setting of rituximab used for the treatment of B cell non Hodgkin's lymphoma (NHL). Age range was 50-74; symptoms were present for 2-24 months and severe pain, heavy discharge and large, deep purulent ulcers extending into the vagina were seen. This article reviews previous reports of vulvovaginal pyoderma gangre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Our literature search yielded 26 articles, which describe 43 cases of PG treated with IVIG (see Fig. and Table S1; see Supporting Information) . The retrospective review identified six patients with PG treated with IVIG at our institutions.…”
Section: Resultsmentioning
confidence: 99%
“…Our literature search yielded 26 articles, which describe 43 cases of PG treated with IVIG (see Fig. and Table S1; see Supporting Information) . The retrospective review identified six patients with PG treated with IVIG at our institutions.…”
Section: Resultsmentioning
confidence: 99%
“…Its use in idiopathic PG has not been reported and paradoxically, rituximab has been implicated as the cause of vulvovaginal PG. 6 These two cases illustrate previously unreported rare skin conditions predating the diagnosis of B-CLL, in which definitive treatment of the primary hematological condition resulted in resolution of these skin manifestations refractory to multiple immunosuppressive treatments. These improvements are postulated to be probably because of an indirect effect of the rituximab and/or multi-agent chemotherapy on the immune dysregulation arising from the malignant B-cell clones rather than a direct therapeutic effect on the skin lesions since in both of our cases, there was a lack of significant B-cell infiltrates in the skin biopsies prior to commencing B-CLL treatment.…”
mentioning
confidence: 70%
“…This includes severe reactions such as toxic epidermal necrolysis. The biologic agent rituximab can cause severe ulceration of the vagina and vestibule . Allergic reactions to topical medications, latex in condoms and semen can also involve the vestibule…”
Section: Dermatological Considerationsmentioning
confidence: 99%